Developing Environmental Awareness of Madrasah Aliyah Students Through the Reading of the Ecological Arabic Poem Hams al-Jufūn by Mikha'il Nu'aymah - Moh. Nurun Nafi’; Pradibyo Herdiansyah (Universitas Islam Negeri Palopo, 2026)
The global environmental crisis demands educational approaches that move beyond cognitive achievement and engage students’ affective, ethical, and spiritual dimensions. This study aims to describe the representation of environmental awareness in the poetry collection Hams al-Jufūn by Mikhā'il Nu‘ayma and to explain its relevance in fostering ecological awareness among students at Madrasah Aliyah Salafiah Sukorejo. The research employs a qualitative approach with a descriptive-interpretative design. Data were collected through textual analysis of the poems, classroom observations, interviews with teachers and students, and documentation review. The analysis was conducted through data reduction, categorization, and interpretation by integrating ecocritical and reader-response perspectives. The findings reveal that the poems in Hams al-Jufūn portray nature as a living entity with moral and spiritual dimensions. Nature is not positioned as a passive background, but as an integral part of life that requires a reciprocal relationship between humans and the environment. The poems also convey subtle criticism of exploitative human behavior through reflective symbols and metaphors. In the classroom context, reading and interpreting the poems significantly contributed to students’ changing perspectives on nature, enhanced emotional engagement and classroom participation, and fostered ethical and religious awareness regarding environmental responsibility. These findings affirm that literature, particularly Arabic poetry, can function as an educational medium that integrates language learning, character formation, and ecological awareness in a holistic manner.